QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)
Number of pages: 24

2012 K.I.D.S Summer Camp - Fequet, Shelley (Coasters Association, 2012)
In the summer of 2006, a six (6) week summer camp pilot project was undertaken in the Municipalities of Bonne Esperance and St. Augustine to provide a Summer Camp for youth. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS”, has proven to be a great success. The mission of KIDS Summer Camp is to nurture and develop a safe and healthy environment in which youth can improve their health and obtain skills that will assist them in their future lives, through physical activities, mental development, artistic growth, environment awareness and community/family participation. In 2007, the Coasters Association expanded the KIDS Summer Camp to two (2) additional communities (La Tabatiere, and Blanc Sablon), as well worked in partnership with, and supported, the Eau-Naturelle Discovery Camp in Chevery, and the two (2) camps already established were maintained. In 2008, 2009, 2010 and 2011 the five camps were in operation and ran very well.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)
Number of pages: 24

Wild Berrylicious : Youth School Kit - Coasters Association (2012)